2016
DOI: 10.1182/blood.v128.22.4766.4766
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Type II Diabetes Mellitus and Hyperlipidemia in Patients Prescribed Dasatinib or Nilotinib As First or Second Line Therapy for Chronic Myelogenous Leukemia (CML)

Abstract: Background: Metabolic changes such as Type II Diabetes Mellitus (T2DM) and hyperlipidemia (HLD) have been reported in patients receiving BCR-ABL tyrosine kinase inhibitor (TKI) therapy. Incidence of metabolic outcomes in this population has not been evaluated in large, real-world studies. The purpose of this study was to determine incidence and risk for T2DM and HLD in commercially and Medicare insured US patients prescribed dasatinib or nilotinib as first or second line therapy for CML. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Oppositely, dasatinib and mostly nilotinib are associated with an increase of cholesterol level. 26 66 77 Nilotinib induces quick rise of total cholesterol, HDL, and LDL (i.e., within 3 months). Nilotinib-induced dyslipidemia are responsive to statin and lipid level normalized after nilotinib discontinuation.…”
Section: Metabolic Dysregulationmentioning
confidence: 99%
“…Oppositely, dasatinib and mostly nilotinib are associated with an increase of cholesterol level. 26 66 77 Nilotinib induces quick rise of total cholesterol, HDL, and LDL (i.e., within 3 months). Nilotinib-induced dyslipidemia are responsive to statin and lipid level normalized after nilotinib discontinuation.…”
Section: Metabolic Dysregulationmentioning
confidence: 99%
“…But it could be attributed to the development of insulin resistance. c‐ABL gene, in in vitro studies, was involved in the insulin receptor (IR) signaling pathway, enhancing the IR metabolic pathway [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…But it could be attributed to the development of insulin resistance. c-ABL gene, in in vitro studies, was involved in the insulin receptor (IR) signaling pathway, enhancing the IR metabolic pathway[21,22].The exudative and chylous nature of the fluid was managed with caution in our patient. With the background of Ph + B-ALL in CR, a new-onset chylothorax would warrant detailed workup, as malignancyinduced thoracic duct obstruction is the leading cause (61% are lymphoproliferative malignancies) and most important differential to be considered in any patient with chylothorax[23].…”
mentioning
confidence: 83%
“…A retrospective cohort study of 1280 patients between 2006 and 2014 demonstrated that patients treated with nilotinib were 1.75 times more likely to develop hyperlipidemia compared to patients treated with dasatinib. 38 Patients being considered for nilotinib should be screened for lipid abnormalities before and early on during therapy. There should be a low threshold for recommending lifestyle intervention and/or initiating medical therapy.…”
Section: Hyperlipidemiamentioning
confidence: 99%